La resistencia de los músculos flexores de los dedos de la mano en escaladores - Nunez, V. M.; Ramirez, J. M.; Lancho, C.; Poblador, M. S.; Lancho, J. L. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2018)
Purpose: To evaluate hand`s fingers flexor muscles grip endurance during a specific climbing test, and to find out if there were differences between elite and recreational sport climbers. Methods: For this cross-sectional descriptive study, twenty-one male sport climbers were assigned to two different groups, recreational or elite. The participants performed two exercises on a multi-hold training board, one requiring sustained isometric exercise and the other requiring intermittent exertion. The variables studied were total work time, number of trials completed and mean heart rate per test. Results: Elite climbers endured suspension for an average of 7.64 minutes being this period longer than recreational climbers (p < .001); thus, elite group performed 23.14 more trials than recreational group (p < .001). Reliability in all evaluations was excellent. Conclusions: Hand`s fingers flexor muscles grip endurance in continuous and intermittent exercises are the muscles that have more influence in sport climbing performance. In this regard, we have found significant differences between elite and recreational climbers.